2016
DOI: 10.1007/s40572-016-0082-3
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Exposure and Immunotoxicity: a Review Including the Possible Influence of Age and Sex

Abstract: Increasing evidence suggests that inorganic arsenic, a major environmental pollutant, exerts immunosuppressive effects in epidemiological, in vitro, and animal models. The mechanisms, however, remain unclear, and little is known about variation in susceptibilities due to age and sex. We performed a review of the experimental and epidemiologic evidence on the association of arsenic exposure and immune diseases. The majority of the studies described arsenic as a potent immunosuppressive compound, though others h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 130 publications
1
47
0
1
Order By: Relevance
“…The observed inverse associations between exposure and infection resistance have been supported by mechanistic and animal studies [912]. Although most of these studies were conducted in populations exposed to high levels of arsenic, our group has recently reported increased susceptibility to infections in those exposed to chronic levels of low to intermediate exposure levels of arsenic [13, 14].…”
Section: Introductionmentioning
confidence: 77%
“…The observed inverse associations between exposure and infection resistance have been supported by mechanistic and animal studies [912]. Although most of these studies were conducted in populations exposed to high levels of arsenic, our group has recently reported increased susceptibility to infections in those exposed to chronic levels of low to intermediate exposure levels of arsenic [13, 14].…”
Section: Introductionmentioning
confidence: 77%
“…A broad range of industrial and environmental chemicals have been suggested to target the immune system . The increased occurrence of immune‐related diseases in recent decades can in part be traced back to the resultant disruption of immune functions .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms behind the immunotoxic effects of arsenic remain unclear (Ahmed et al 2014; Ferrario et al 2016). One potential mechanism is that arsenic could interfere with the expression of immune-related genes.…”
Section: Introductionmentioning
confidence: 99%